Level of antiretroviral therapy adherence and associated factors during COVID-19 pandemic era in public hospitals of Jigjiga City eastern Ethiopia: a cross-sectional study - Tesfay, Samson; Ayele, Firayad; Fissahaye, Birhane; Asmerom, Haftu; Gebremichael, Berhe (Frontiers in Public Health, 2024)
Background Coronavirus-19 disease is more severe in patients on antiretroviral therapy (ART). Low-income countries, such as those in Sub-Saharan Africa, are particularly vulnerable to the virus’ spread. However, there is little information on antiretroviral therapy (ART) use in Ethiopia during the pandemic, particularly in the study area. Therefore, this study aimed to assess the level of antiretroviral treatment adherence and associated factors during the COVID-19 pandemic era in public hospitals in Jigjiga City, Somalia, and Eastern Ethiopia. Methods An institution-based cross-sectional study was conducted among 382 randomly selected HIV patients on antiretroviral therapy (ART) follow-up in public hospitals in Jigjiga City from March 1–30, 2022. The data was collected through face-to-face interviews and a review of the patient’s record. To explore the relationship between variables, both bivariate and multivariable logistic regression analyses were performed. The adjusted odds ratio (AOR) was utilized, along with a 95% confidence interval, to assess the strength and direction of the association. Statistical significance was considered at p < 0.05. Results The antiretroviral therapy (ART) adherence rate of HIV patients was 76.9% (95% CI, 71.9–82). Disclosing HIV status to sexual partners [AOR = 2.3, (95% CI (1.22–4.19)], having communication with health care providers’ [AOR = 3.2, (95% CI (1.57–6.53)], having no history of current substance use [AOR = 2.6, (95% CI (1.45–4.63)], and patients who did not fear COVID-19 infection [AOR = 5.8 (95% CI (11–10.98)] were significantly associated with antiretroviral therapy (ART) adherence. Conclusion In this study, the level of antiretroviral therapy (ART) adherence was poor in comparison to the expected level. Patients’ adherence status was favorably related to disclosing their status to families and having contact with their healthcare providers, whereas worrying about COVID-19 pandemic infection and current substance use was adversely associated.